Association between hypoalbuminemia and hypophosphatemia with malnutrition in patients with chronic renal disease undergoing hemodialysis - Castillo Velarde, Edwin (2020)
Introduction: Malnutrition in hemodialysis patients is a consequence of various deficiency andhypercatabolic factors and constitutes a risk factor for morbidity and mortality. Objective: Determinethe association between hypoalbuminemia and hypophosphatemia with the Subjective globalassessment (SGA) C in patients with chronic renal disease on hemodialysis. Methods: Analytical cross-sectional study. Patients from the hemodialysis service of the Hospital Guillermo Almenara werestudied. The Kruskal-Wallis test and multiple comparisons test were used for the association betweencontinuous variables of malnutrition and the types of SGA. The square-chi test was used for thecategorical variables hypoalbuminemia (≤3.5 g/dL) and hypophosphatemia (<3 mg/dL). The associationwith SGA C was analyzed. Results: 131 patients were included and the median age was 63 years. 34%had hypoalbuminemia, 27% had hypophosphatemia and 14% had SGA C. 52% (68) of the patientspresented alteration of at least one analyzed biomarker. Differences were found between SGA andalbumin (p<0.001) and phosphorus (p=0.040). Patients with SGA C had a mean albumin of 3.1±0.74 andphosphorus of 2.88±1.54 and had a significant difference compared to those with SGA A (p<0.001 and P= 0.011, respectively). Chi-square analysis also demonstrated a significant association between SGA andhypoalbuminemia (p = 0.017) and hypophosphatemia (p=0.050). Conclusion: There is an associationbetween SGA C and hypoalbuminemia and hypophosphatemia in patients with chronic kidney diseaseundergoing hemodialysis.